Study of knowledge, attitude and acceptance of PPIUCD in antenatal mothers - Pradeep MR; Nayana DH (Barpeta Obstetrics and Gynaecological Society, 2019)
Objectives: To find out the knowledge attitude and acceptance of post partum intrauterine contraceptive device (PPIUCD) among antenatal mothers. Methodology: This is an observational study to assess knowledge, attitude and acceptance of PPIUCD by antenatal mothers with family members by pre counseling and post counseling questionnaire. Results: A total of 137 antenatal mothers were studied from October 2018 to December 2018. Number of primi and multigravida were almost same in the study. Prior knowledge regarding PPIUCD was only in 15.3%. About 51.8 % accepted for PPIUCD after counseling. Most common reason in 66.7% for non acceptance was fear of complications. Conclusion: Knowledge on PPIUCD of our antenatal mothers is poor. Counseling of antenatal women and their families is helpful for high acceptance of PPIUCD.